Lithium-rich cobalt-doped lithium ion battery positive electrode material and preparation method thereof

The composite sintering method of nickel hydroxide manganese and cobalt hydroxide and lithium sources is prepared to prepare the positive electrode material of lithium cobalt doped lithium -ion battery, which solves the problem of poor heat stability in the long cycle and high temperature of existing materials, and achieves higher heat stability, and has achieved higher higher thermal stability, and has achieved higher higher thermal stability, and has achieved higher higher heat stability, and has achieved higher higher heat stability, and has achieved higher higher heat stability, and has achieved higher higher heat stability, and has achieved higher higher heat stability, and has achieved higher higher heat stability. Circulation stability, multiplier performance and safety.

CN119361681AActive Publication Date: 2025-01-24CHANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411493334.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials are prone to structural reconstruction, particle rupture, transition metal ion dissolution and cathode-electrolyte interface film during long cycles, and have poor thermal stability at high temperatures, which can easily lead to fire and explosion accidents.

Method used

Nickel hydroxide manganese front -driven Ni0.5MN0.5 (OH) 2. CO (OH) 2 and lithium -source composite sintering to prepare lithium cobalt -doped lithium -ion battery positive electrode materials, and the manufacturing cost of the material is regulated The stability of the structure of the crystal, inhibit the side reaction of the interface, and improve its own thermal safety.

Benefits of technology

It significantly improves the cycle stability, magnification performance and safety characteristics of lithium -ion batteries, delay the heat out of control of the battery, and reduce the possibility of the battery thermal control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361681A_ABST
    Figure CN119361681A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a lithium-rich cobalt-doped lithium ion battery positive electrode material and a preparation method thereof. The lithium-rich cobalt-doped lithium ion battery positive electrode material is composed of a nickel manganese hydroxide precursor Ni0. 5Mn0. 5 (OH) 2, a cobalt hydroxide precursor Co (OH) 2 and a lithium source, and the positive electrode material can be prepared through the working procedures of mixed ball milling, low-temperature sintering and grinding. According to the lithium-rich cobalt-doped lithium ion battery positive electrode material disclosed by the invention, the cycle performance and the rate capability of a lithium ion battery at a high voltage of 3.0-4.5 V can be obviously improved, the thermal stability of the positive electrode material is optimized, the reversible capacity of the positive electrode material is effectively improved, and the purposes of reducing the manufacturing cost, improving the electrochemical performance and improving the safety performance of the battery are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a lithium-rich cobalt-doped lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] With the continuous deepening of research on lithium-ion cathode materials, in order to meet the market's pursuit of high energy density of nickel cobalt manganese oxide (NCM) materials, many methods have been proposed, such as: introducing new elements through doping or coating to improve the kinetic properties of the material, changing the original metal elements to increase the battery capacity, and optimizing the morphology of the material to improve the energy density. Previous studies on the comprehensive performance and structural evolution of NCM materials with different transition metal ratios show that LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) exhibits excellent comprehensive performance. The 50% nickel content gives it a good reversible capacity during the cycle process. Due to the relatively low nickel content, the cycle stability and thermal safety performance are also relatively excellent. It is the most commercially valuable and potential alternative material to lithium iron phosphate in the NCM system.

[0003] Nevertheless, high costs and supply chain shortages of raw materials have forced people to find ways to eliminate or replace 20% of the cobalt in NMC523 to achieve similar battery performance. According to theoretical calculations, when Co in NMC523 is replaced with Mn, the resulting layered oxide LiNi 0.5 Mn 0.5 O2 still has a theoretical capacity of 280 mAh / g, confirming that LiNi 0.5 Mn 0.5 O2 is a viable alternative to LiCoO2. However, LiNi 0.5 Mn 0.5O2 cannot reach the theoretical capacity because the presence of manganese ions promotes the cation mixing of Li / Ni, resulting in the ion diffusion of lithium ions in the layered structure being hindered. In order to solve this dilemma, Chinese patent CN111162322A enhances its lithium storage performance and improves the battery's cycle and rate performance by constructing a nickel-manganese oxide with a porous nanosheet structure. Chinese patent CN107591519A performs grain boundary doping on conventional lithium nickel-cobalt-manganese positive electrode materials, so that the modified lithium nickel-cobalt-manganese positive electrode materials still have a very stable structure during repeated charge and discharge of strong currents. Chinese patent CN201510026729 uses ultrasonic chemical nickel plating to achieve uniform surface coating modification of lithium nickel manganese oxide materials. The formed nickel coating, as an excellent conductor, can greatly improve the conductivity of the material after coating, which is beneficial to the improvement of the material's rate performance and cycle performance. Although similar control methods can effectively improve the structural stability and cycle performance of nickel-manganese oxide lithium-ion batteries, they are still far from the actual application requirements, and the process is cumbersome and costly. It is difficult for current positive electrode materials to balance the electrochemical properties such as manufacturing cost, capacity, internal resistance and their own safety.

[0004] The ternary cathode materials in the prior art have the following problems: structural reconstruction, particle rupture, transition metal ion dissolution, and cathode-electrolyte interface film damage are prone to occur during long-term cycling. The oxide cathode in a highly delithiation state has extremely poor thermal stability and is easily decomposed to produce oxygen at high temperatures, resulting in severe oxidation of the electrolyte on the cathode surface, releasing a large amount of heat and generating a large amount of gas, which in severe cases may cause serious fires and explosions in the battery. Therefore, it is necessary to develop a lithium-ion battery cathode material with stable structure, excellent performance, and high safety. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a lithium-rich cobalt-doped lithium-ion battery positive electrode material and a preparation method thereof. The lithium-rich cobalt-doped lithium-ion battery positive electrode material of the present invention has a stable structure, excellent performance and high safety, regulates the manufacturing cost of the positive electrode material, improves the crystal structure stability under high voltage, inhibits interface side reactions, improves its own thermal safety, reduces the possibility of thermal runaway of the battery, and thus improves the cycle stability, rate performance and safety characteristics of the lithium-ion battery.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A lithium-rich cobalt-doped lithium-ion battery positive electrode material, comprising a nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2, cobalt hydroxide precursor Co(OH)2 and lithium source are compositely sintered to obtain the nickel manganese hydroxide precursor Ni 0.5 Mn0.5 The weight portion of (OH)2 is 60 to 75 parts, the weight portion of the cobalt hydroxide precursor Co(OH)2 is 0 to 5 parts, and the weight portion of the lithium source is 25 to 35 parts.

[0008] Furthermore, the lithium source is LiOH·H2O or Li2CO3.

[0009] Furthermore, the sintering method is a tubular furnace in an oxygen atmosphere or a muffle furnace in an air atmosphere.

[0010] Furthermore, the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The (OH)2 particle size is 25μm, 50μm, 100μm, 200μm, and 400μm.

[0011] Furthermore, the particle size of the cobalt hydroxide precursor Co(OH)2 is one of 25 μm, 50 μm, 100 μm, 200 μm and 400 μm.

[0012] A method for preparing the above-mentioned lithium-rich cobalt-doped lithium-ion battery positive electrode material specifically comprises the following steps:

[0013] Step S1, weighing nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2, cobalt hydroxide precursor Co(OH)2 and lithium source;

[0014] Step S2: nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 After briefly mixing cobalt hydroxide precursor Co(OH)2, the precursor material was obtained by placing the cobalt hydroxide precursor Co(OH)2 in a mechanical mixing device for 1 h.

[0015] Step S3, putting the precursor material and the lithium source into a mortar and grinding for 10 minutes to obtain a mixed powder;

[0016] Step S4, putting the mixed powder into a sample pool, and then placing it in a sintering furnace, sintering for 20 hours to obtain a primary product;

[0017] Step S5, putting the primary product into a mortar and grinding for 2 minutes to obtain a finished product of lithium-rich cobalt-doped lithium-ion battery positive electrode material.

[0018] Furthermore, in step S4, the sintering temperature is 400°C.

[0019] The beneficial effects of the present invention are as follows: the present invention has a reasonable design, a simple preparation method, and has the following advantages:

[0020] (1) The lithium-rich cobalt-doped lithium-ion battery positive electrode material of the present invention can significantly improve the cycle performance of nickel-manganese oxide lithium-ion batteries at high voltages between 3.0 and 4.5 V. Compared with existing positive electrode materials, the specific capacity of the battery is increased to 180.00 mA / g, and the capacity retention rate is increased to 98%;

[0021] (2) The lithium-rich cobalt-doped lithium-ion battery positive electrode material of the present invention can improve the thermal stability of the positive electrode material itself and increase the thermal decomposition reaction temperature of the positive electrode material, thereby slowing down the thermal runaway speed of the battery and improving the safety performance of the battery;

[0022] (3) The lithium-rich cobalt-doped lithium-ion battery positive electrode material of the present invention can significantly improve the rate performance of the material. During high-rate discharge, the capacity of the lithium-rich material exceeds three times that of existing positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 A comparison chart of rate performance and cycle efficiency curves of half cells assembled from Example 2, Comparative Example 1 and Comparative Example 2 of the present invention;

[0025] Figure 2 A comparison chart of lithium ion diffusion coefficients of half-cells assembled in Example 2 and Comparative Example 1 of the present invention;

[0026] Figure 3 1 is a cyclic stability curve diagram of Example 3 and Comparative Example 1 in the present invention;

[0027] Figure 4 It is a comparison diagram of thermogravimetric TG analysis curves of the positive electrode materials in Example 2, Comparative Example 1 and Comparative Example 3 of the present invention;

[0028] Figure 5 It is a comparison diagram of thermal analysis DSC curves of the positive electrode materials in Examples 1, 2, 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0029] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] A lithium-rich cobalt-doped lithium-ion battery positive electrode material, comprising a nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2, cobalt hydroxide precursor Co(OH)2 and lithium source are compositely sintered to obtain the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The weight portion of (OH)2 is 60 to 75 parts, the weight portion of the cobalt hydroxide precursor Co(OH)2 is 0 to 5 parts, and the weight portion of the lithium source is 25 to 35 parts.

[0033] The lithium source is LiOH·H2O or Li2CO3; the sintering method is a tubular furnace in an oxygen atmosphere or a muffle furnace in an air atmosphere.

[0034] Nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The particle size of (OH)2 is one of 25μm, 50μm, 100μm, 200μm and 400μm; the particle size of cobalt hydroxide precursor Co(OH)2 is one of 25μm, 50μm, 100μm, 200μm and 400μm.

[0035] A method for preparing the above-mentioned lithium-rich cobalt-doped lithium-ion battery positive electrode material specifically comprises the following steps:

[0036] Step S1, weighing nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2, cobalt hydroxide precursor Co(OH)2 and lithium source;

[0037] Step S2: nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 After briefly mixing cobalt hydroxide precursor Co(OH)2, the precursor material was obtained by placing the cobalt hydroxide precursor Co(OH)2 in a mechanical mixing device for 1 h.

[0038] Step S3, putting the precursor material and the lithium source into a mortar and grinding for 10 minutes to obtain a mixed powder;

[0039] Step S4, putting the mixed powder into a sample pool, and then placing it in a sintering furnace, sintering for 20 hours at a sintering temperature of 400° C. to obtain a primary product;

[0040] Step S5, putting the primary product into a mortar and grinding for 2 minutes to obtain a finished product of lithium-rich cobalt-doped lithium-ion battery positive electrode material.

[0041] Example 1

[0042] A method for preparing a lithium-rich cobalt-doped lithium-ion battery positive electrode material specifically comprises the following steps:

[0043] Step S1, weighing nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2 60 parts, cobalt hydroxide precursor Co(OH)2 5 parts and lithium source Li2CO3 35 parts. Among them, nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The particle sizes of (OH)2 and cobalt hydroxide precursor Co(OH)2 were 25 μm, respectively;

[0044] Step S2: nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 After briefly mixing cobalt hydroxide precursor Co(OH)2, the precursor material was obtained by placing the cobalt hydroxide precursor Co(OH)2 in a mechanical mixing device for 1 h.

[0045] Step S3, putting the precursor material and the lithium source into a mortar and grinding for 10 minutes to obtain a mixed powder;

[0046] Step S4, putting the mixed powder into a sample pool, and then placing it in a tube furnace in an oxygen atmosphere, sintering for 20 hours at a sintering temperature of 400° C. to obtain a primary product;

[0047] Step S5, putting the primary product into a mortar and grinding for 2 minutes to obtain a finished product of lithium-rich cobalt-doped lithium-ion battery positive electrode material.

[0048] A manufacturing process of a positive electrode sheet is as follows: a lithium-rich cobalt-doped lithium-ion battery positive electrode material, a conductive agent acetylene black, and a binder polyvinylidene fluoride (PVDF) are mixed according to a mass ratio of positive electrode material: acetylene black: polyvinylidene fluoride = 8:1:1, and after mixing, N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to form a uniform positive electrode slurry and evenly coated on a 15μm thick aluminum foil, and then dried at 120°C in a forced air drying oven for 12 hours to obtain a positive electrode sheet for use.

[0049] The manufacturing process of a positive electrode half-cell is as follows: the above-mentioned positive electrode sheet is used as the positive electrode, the metal lithium sheet is used as the negative electrode, Celgard 2500 is used as the separator, an electrolyte is added, and a button-type half-cell with a battery model of CR2032 is assembled in a glove box.

[0050] The battery cycle test steps are as follows:

[0051] The assembled button half-cell was left at room temperature (25°C) for 12 hours and then cycled, with a charge and discharge voltage of 3.0 to 4.5 V. The battery was first charged and discharged for three cycles at a current of C / 20, and then for 50 to 100 cycles at a current of C / 5.

[0052] The test procedure is: C / 20 constant current charging to 4.5V, and then C / 20 discharge to 3.0V. After fully activating the electrode material, the battery is charged and discharged for 100 cycles at C / 5 to evaluate the cycle stability. After every 50 cycles, the battery is cycled once at a rate of C / 20 for inspection.

[0053] The battery rate performance test steps are as follows:

[0054] The assembled button half-cell was left at room temperature (25°C) for 12 h, and then cycle and rate tests were performed, with a charge and discharge voltage of 3.0 to 4.5 V. The battery was first charged and discharged for two cycles at a current of C / 20, then charged at a current of C / 20, and then discharged at 5 different increasing rates in sequence.

[0055] The test procedure is: C / 20 constant current charging to 4.5V, and then C / 20 discharge to 3.0V. After fully activating the electrode material, charge at C / 20 current, and then discharge at increasing rates of C / 20, C / 5, C / 2, 1C and 2C in sequence, so as to obtain the reversible capacity of the battery at different rates to evaluate the rate performance of the battery.

[0056] The thermogravimetric testing process is as follows:

[0057] After the cycle is completed, the battery is disassembled in the glove box, the positive electrode sheet is separated, and the positive electrode sheet is cleaned with dimethyl carbonate solvent to remove the residual electrolyte and left to dry. The electrode material is scraped off the aluminum sheet, and 5 mg of the electrode sheet is weighed and placed in the sample cell. A thermogravimetric experiment is performed on the thermal analyzer with a heating range of 100-550°C and a heating rate of 10.0°C / min, and the mass change curve of the positive electrode material during the heating process is recorded. For comparison, TG experiments are performed separately on different positive electrode material samples.

[0058] The thermal analysis test process is as follows:

[0059] The cathode material was obtained by the same pretreatment method as the TG test, and 8 mg of the cathode piece was weighed and placed in the sample cell. A differential scanning calorimeter DSC experiment was performed on the thermal analyzer with a heating range of 100-800°C and a heating rate of 10.0°C / min, and the heat generation curve of the cathode material during the heating process was recorded. For comparison, DSC experiments were performed on different cathode material samples separately.

[0060] Example 2

[0061] The difference from Example 1 is that the lithium-rich cobalt-doped lithium-ion battery positive electrode material of this embodiment is made of nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2 and lithium source are compositely sintered to obtain the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The weight of (OH)2 is 65 parts, the particle size is 25 μm, and the weight of the lithium source Li2CO3 is 35 parts.

[0062] The positive electrode material and positive electrode half-cell were prepared by the same method as in Example 1, and the cycle performance, rate performance, ion diffusion coefficient and thermal stability tests were carried out.

[0063] The lithium ion diffusion coefficient test process is as follows:

[0064] The Atlung method of intermittent diffusion (AMID) was used to test the battery using a voltage window of 3.0-4.5V in the first cycle, followed by charging to 4.5V at C / 40. The subsequent discharge was performed at a continuous rate of 5C, 3C, 2C, 1C, C / 2.5, C / 5, C / 10, C / 20, C / 40, C / 80, and C / 160, with an OCV of 1h between each C rate, first 4.5-4.3V as an interval, then 4.3V-3.6V divided into 7 voltage intervals at intervals of 0.1V, and 3.6-3.0V as a single interval. The lithium ion diffusion coefficient in different voltage intervals was obtained by calculation.

[0065] Example 3

[0066] The difference from Example 1 is that in the lithium-rich cobalt-doped lithium-ion battery positive electrode material of this embodiment, the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The weight of nickel manganese hydroxide precursor Ni is 75 parts, the weight of cobalt hydroxide precursor Co(OH)2 is 2 parts, and the weight of lithium source Li2CO3 is 25 parts. 0.5 Mn 0.5 The particle size of (OH)2 is 400μm, and the particle size of cobalt hydroxide precursor Co(OH)2 is 200μm.

[0067] The positive electrode material and button-type half-cell were prepared in the same manner as in Example 1, and the cycle performance and thermal stability tests were performed.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that in the battery positive electrode material of this comparative example, the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The weight of (OH)2 is 75 parts, and the weight of lithium source Li2CO3 is 25 parts. Among them, the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The particle size of (OH)2 is 400μm; the particle size of cobalt hydroxide precursor Co(OH)2 is 200μm.

[0070] The positive electrode material and positive electrode half-cell were prepared by the same method as in Example 1, and the cycle performance, rate performance, ion diffusion coefficient and thermal stability tests were carried out.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that in the battery positive electrode material of this comparative example, the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The weight of (OH)2 is 70 parts, the particle size is 100 μm, and the weight of the lithium source Li2CO3 is 30 parts.

[0073] The positive electrode material and positive electrode half-cell were prepared in the same manner as in Example 1, and the cycle performance and rate performance tests were performed.

[0074] Comparative Example 3

[0075] The difference from Example 1 is that the positive electrode material of the battery in this comparative example is a ternary positive electrode material in the prior art.

[0076] The positive electrode material and positive electrode half-cell were prepared in the same manner as in Example 1, and a thermal stability test was performed.

[0077] from Figure 1It can be seen that when the weight of the lithium source is increased from 25 parts to 35 parts in Example 2 and Comparative Example 1 compared with Comparative Example 2, the rate performance of the battery is significantly improved, and the discharge capacity is significantly improved. At a current rate of 2C, the capacity increases from 40mAh / g in Comparative Example 1 to 140mAh / g in Example 2, and Example 2 is less affected by the current rate. In addition, the cycle performance results of the three positive electrode half-cells show that the reversible capacity of the three positive electrode materials also shows a gradient increase trend. And after long-term cycling, the capacities of Comparative Example 1, Comparative Example 2 and Example 2 decreased by and 16%, 19% and 6%, respectively. It can be seen that Example 2 has a greater advantage in cycle stability.

[0078] from Figure 2 It can be seen from the results of the lithium ion diffusion coefficient in Example 2 that the ion diffusion capacity of Example 2 is improved by nearly 2 orders of magnitude compared with that of Comparative Example 1. The lithium ions in the material can migrate rapidly in the structure, which fully reflects the Figure 1 Therefore, the lithium-rich cobalt-doped lithium-ion battery positive electrode material of the present invention can significantly improve the electrochemical performance by enhancing the lithium ion diffusion kinetics.

[0079] Figure 3 The embodiment 3 doped with cobalt is compared with the comparative example 1 without cobalt doping, and the cycle stability test under the same voltage range and current rate is performed. It can be found that compared with the comparative example 1, the cycle capacity loss of the embodiment 3 is further reduced, and more than 98% of the capacity can be maintained after 100 cycles. This shows that the cobalt element doped in the embodiment 3 can fully stabilize the internal structure of the positive electrode material, so that the material remains stable in the long cycle of charge and discharge, and effectively prolongs the battery life.

[0080] In terms of thermal safety performance, whether it is Figure 4 The TG test results are still Figure 5 According to the DSC test results, the lithium-rich cobalt-doped positive electrode materials corresponding to Example 1 all exhibited good thermal stability. Figure 4 In the thermogravimetric curve comparison diagram, the mass loss of comparative example 3 in the same temperature range is about dozens of times that of example 2. Not only that, the starting temperature of its mass loss is also nearly 100°C lower than that of example 2, showing extremely strong structural instability, which is very unfavorable for maintaining the overall safety of the battery. In addition, Figure 5In the comparison of heat generation rates, the heat generation rate of Example 3 doped with cobalt element is significantly lower than that of Comparative Example 1, and the corresponding heat generation is also greatly reduced. Comparing Example 2 with Comparative Example 1, the addition of excess lithium element can also play a similar role. Taking into account the synergistic effect of excess lithium and doped cobalt elements, the heat generation rate and heat generation in Example 1 are the lowest. Therefore, the lithium-rich cobalt-doped positive electrode material can maximize the stability of the material, thereby reducing the heat generation of the positive electrode material and effectively inhibiting the starting reaction of thermal runaway of the battery.

[0081] In summary, the lithium-rich cobalt-doped nickel-manganese oxide positive electrode material of the present invention not only enhances the lithium ion diffusion capacity inside the positive electrode structure, but also can inhibit the adverse structural transformation of the material; synergistically combines the effects of excess lithium elements and trace cobalt doping to form a high-quality stable symbiotic crystal structure inside the material, which protects the structural integrity of the electrode material while inhibiting the occurrence of side reactions, thereby improving the cycle performance and rate performance of the battery at high voltage; and realizes that the lithium-ion battery has good safety performance while having high voltage and excellent electrochemical properties.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-rich cobalt-doped lithium-ion battery positive electrode material, characterized in that: The lithium-rich cobalt-doped lithium-ion battery positive electrode material is composed of a nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2, cobalt hydroxide precursor Co(OH)2 and lithium source are compositely sintered to obtain the nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The weight portion of (OH)2 is 60 to 75 parts, the weight portion of the cobalt hydroxide precursor Co(OH)2 is 0 to 5 parts, and the weight portion of the lithium source is 25 to 35 parts.

2. The lithium-rich cobalt-doped lithium-ion battery positive electrode material according to claim 1, characterized in that: The lithium source is LiOH·H2O or Li2CO3.

3. The lithium-rich cobalt-doped lithium-ion battery positive electrode material according to claim 1, characterized in that: The sintering method is a tubular furnace in an oxygen atmosphere or a muffle furnace in an air atmosphere.

4. The lithium-rich cobalt-doped lithium-ion battery positive electrode material according to claim 1, characterized in that: The nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 The (OH)2 particle size is 25μm, 50μm, 100μm, 200μm, and 400μm.

5. The lithium-rich cobalt-doped lithium-ion battery positive electrode material according to claim 1, characterized in that: The particle size of the cobalt hydroxide precursor Co(OH)2 is one of 25 μm, 50 μm, 100 μm, 200 μm and 400 μm.

6. A method for preparing a lithium-rich cobalt-doped lithium-ion battery positive electrode material as claimed in any one of claims 1 to 5, characterized in that: The specific steps include: Step S1, weighing nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 (OH)2, cobalt hydroxide precursor Co(OH)2 and lithium source; Step S2: nickel manganese hydroxide precursor Ni 0.5 Mn 0.5 After briefly mixing cobalt hydroxide precursor Co(OH)2, the precursor material was obtained by placing the cobalt hydroxide precursor Co(OH)2 in a mechanical mixing device for 1 h. Step S3, putting the precursor material and the lithium source into a mortar and grinding for 10 minutes to obtain a mixed powder; Step S4, putting the mixed powder into a sample pool, and then placing it in a sintering furnace, sintering for 20 hours to obtain a primary product; Step S5, putting the primary product into a mortar and grinding for 2 minutes to obtain a finished product of lithium-rich cobalt-doped lithium-ion battery positive electrode material.

7. The method for preparing a lithium-rich cobalt-doped lithium-ion battery positive electrode material according to claim 6, characterized in that: In the step S4, the sintering temperature is 400°C.

Citation Information

Patent Citations

  • Layered lithium-rich manganese oxide positive electrode material capable of effectively improving rate capability and preparation method and application thereof

    CN111732125A

  • Lithium ion battery composite positive electrode material and preparation method thereof

    CN112310353A

  • Cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN116639740A

  • Lithium-rich manganese-based positive electrode material, preparation method thereof, positive electrode and battery

    CN118579850A

  • Cathode active material for lithium ion secondary batteries, method for manufacturing the same, and lithium ion secondary batteries including the same

    KR1020180076601A